Estudio de Factibilidad para la Implementación de una Caja de Ahorro en el Barrio la Era, Parroquia El Tambo, Cantón Catamayo, Provincia de Loja - Pérez V, Gabriela Alexandra (2016)
For the realization of this project "FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A BOX OF SAVINGS IN THE NEIGHBORHOOD LA ERA, PARISH EL TAMBO, CATAMAYO CANTON, PROVINCE OF LOJA”, it was necessary to carry out a market study, technical study law firm - Administrative and financial evaluation, which allowed to know the feasibility of the proposal. To achieve the first objective was collecting information needed by the application of surveys, with which we proceeded to calculate the claims. The potential demand represented by the total market study which comprise 717 people, of which 86.61% are active members of a financial institution getting a real demand for 621 people. Effective demand made by people who wish to be future partners of the Fund Savings equivalent to 99.03% the 615 potential partners. The offer consists of the total number of institutions that provide financial services, however it took into account the 75 partners who have an active account in the community bank located in the parish of El Tambo and this has similar characteristics to the box and is the nearest to the new financial institution entity. The unmet demand corresponding to the effective demand less total supply (615-75) obtaining a total of 540 people who are unhappy with the service you are using, demonstrating the acceptance of the inhabitants by the existence of a Box saving. - 6 Through a technical study, it was met for the second objective in which the project location is determined, as well as established 100% capacity utilization in relation to the installed capacity because it can not limit the number partners and the amount of savings the design of the plant where physical layout of each of the offices where they carry out financial activities and processes shown also shown, and equipment needed for the operation was performed box. The third goal allowed developing the legal and administrative organization of the box, just as the respective charts and manuals functions which allow partners to assure that the company is well organized and there is excellent coordination between the different areas were made and the team With the completion of the financial economic study the fourth objective, in which the initial investment project which has a value of $ 23,405.59 was determined fulfilled. The calculations to determine the NPV of the project is $ 28,782.10 and representing 44.76% IRR were performed; RBC 1.70 for every dollar invested which indicate that the investment project is feasible, also the sensitivity analyzes are positive indicating that the project profitable